The Mechanism of Allosteric Coupling in Choline Kinase α1 Revealed by the Action of a Rationally Designed Inhibitor1. Issue 17 (25th February 2013) - Sahún‐Roncero, María; Rubio‐Ruiz, Belén; Saladino, Giorgio; Conejo‐García, Ana; Espinosa, Antonio; Velázquez‐Campoy, Adrián; Gervasio, Francesco Luigi; Entrena, Antonio; Hurtado‐Guerrero, Ramon
<x xml:space="preserve">Abstract</x> Applying a CHOK hold: Combined experimental and computational studies of the binding mode of a rationally designed inhibitor of the dimeric choline kinase α1 (CHOKα1) explain the molecular mechanism of negative cooperativity (see scheme) and how the monomers are connected. The results give insight into how the symmetry of the dimer can be partially conserved despite a lack of conservation in the static crystal structures.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>